2010
DOI: 10.1136/aim.2009.001867
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Acupuncture on the Sleep Pattern of Patients with Obstructive Sleep Apnoea

Abstract: Background Most patients with obstructive sleep apnoea (OSA) do not tolerate treatment with nasal continuous positive airway pressure, the 'gold standard' treatment for this condition. It was shown in a pilot study that acupuncture was more effective than placebo treatment (sham acupuncture) in producing signifi cant changes in the respiratory events assessed by polysomnography (PSG). Objectives To investigate the immediate effect of manual acupuncture (MA) and electroacupuncture (EA) on the sleep pattern of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
0
23
3
1
Order By: Relevance
“…In our study, no changes, either in AHI or SatO 2 , were observed. Some points may have contributed to the divergent findings between our investigation and other studies (Freire et al, , ; Lv et al, ). First, the number of patients receiving treatment in our study was significantly higher than in the studies by Freire et al (, [10 in acupuncture and 10 in sham]), which, in turn, could reflect more reliable data.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…In our study, no changes, either in AHI or SatO 2 , were observed. Some points may have contributed to the divergent findings between our investigation and other studies (Freire et al, , ; Lv et al, ). First, the number of patients receiving treatment in our study was significantly higher than in the studies by Freire et al (, [10 in acupuncture and 10 in sham]), which, in turn, could reflect more reliable data.…”
Section: Discussioncontrasting
confidence: 79%
“…Some points may have contributed to the divergent findings between our investigation and other studies (Freire et al, , ; Lv et al, ). First, the number of patients receiving treatment in our study was significantly higher than in the studies by Freire et al (, [10 in acupuncture and 10 in sham]), which, in turn, could reflect more reliable data. Second, only two of the six studies included in the meta‐analysis by Lv et al () adopted the same methodology as our study (i.e., acupuncture versus control and/or sham), thus limiting the conclusions of their findings.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Next, trials that used EA adjunctively to MA (designated as MA versus MA + EA) were differentiated from trials that directly compared the two procedures (MA versus EA). If all procedures in the EA group before electrostimulation were the same as procedures in the MA group (e.g., de qi was initially elicited in each group), the trial was considered MA versus MA + EA; if the pre-electrostimulation procedure in the EA group was different (e.g., if de qi was elicited only in the MA group), the trial was considered MA versus EA.…”
Section: Clinical Trials Comparing Ma and Eamentioning
confidence: 99%